Book Review of: Cornwell, D. Blad, J. and Wright, M. (2013) Civilising Criminal Justice. An International Restorative Agenda for Penal Reform. Sherfield Gables: Waterside Press. (2014) - Chankova, Dobrinka
No abstract available